Діджиталізація в мовах інтеграції України в Європейський Союз - Кириченко, Микола; Отамась, Інна (Видавництво Львівської політехніки, 2020)
The article analyzes the national legal framework for e-government, in particular for ensuring information security of the state. The organizational and legal mechanisms of development of the electronic format of activity of the state bodies developed within the limits of electronic government in Ukraine till 2020 are considered. Among which: open data; electronic services; electronic identification; electronic interaction; formation of quality information policy; promoting integration into the EU Digital Single Market. Ukraine’s entry into the single information space and the creation of the Central State Electronic Archive of Ukraine (CDEA of Ukraine). The main Directives of the European Parliament and of the Council on electronic identification and trust services for the purposes of electronic transactions in the internal market are considered.
Keywords: електронне урядування; інформаційна безпека; інформаційне суспільство